2003
DOI: 10.1002/jnr.10542
|View full text |Cite
|
Sign up to set email alerts
|

BDNF‐induced survival of auditory neurons in vivo: Cessation of treatment leads to accelerated loss of survival effects

Abstract: Neurotrophic factors are important for the development and maintenance of the auditory system. They have also been shown to act as survival factors for auditory neurons in animal deafness models. Studies have demonstrated recently that these neurotrophic factors not only maintain survival of auditory neurons, but that these surviving neurons retain functionality. It remains to be determined, however, if a single administration of a neurotrophic factor is sufficient to maintain auditory neuron survival after lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
164
4
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(187 citation statements)
references
References 36 publications
18
164
4
1
Order By: Relevance
“…As mentioned previously, several recent in vivo studies have reported that direct cochlear infusion of neurotrophins (NTs), particularly BDNF, can promote improved SG survival following deafness (Gillespie et al, 2003;Miller et al, 1997;Miller et al, 2007;Shinohara et al, 2002;Staecker et al, 1996). Further, ICES has been reported to be additive to the effects of NTs (Kanzaki et al, 2002;Shepherd et al,2005;Pettingill et al, 2007) in reducing SG degeneration.…”
Section: Intracochlear Infusion Of Neurotrophinsmentioning
confidence: 92%
See 1 more Smart Citation
“…As mentioned previously, several recent in vivo studies have reported that direct cochlear infusion of neurotrophins (NTs), particularly BDNF, can promote improved SG survival following deafness (Gillespie et al, 2003;Miller et al, 1997;Miller et al, 2007;Shinohara et al, 2002;Staecker et al, 1996). Further, ICES has been reported to be additive to the effects of NTs (Kanzaki et al, 2002;Shepherd et al,2005;Pettingill et al, 2007) in reducing SG degeneration.…”
Section: Intracochlear Infusion Of Neurotrophinsmentioning
confidence: 92%
“…However, studies to date have been conducted in rodents and are limited to quite short durations (e.g., 30 days). Little is known about the longterm effects of NTs, and one animal study has suggested that accelerated SG degeneration occurs after cochlear infusion of BDNF is terminated (Gillespie et al, 2003). Therefore, we are interested in studying neurotrophic effects over longer durations, and in different animal models that may better represent the slower time course of SG degeneration in the human cochlea.…”
Section: Intracochlear Infusion Of Neurotrophinsmentioning
confidence: 99%
“…Extended periods of delivery are likely to result in greater cell survival and a more stable connection between the synthetic materials and biological tissue. Gillespie et al have shown that release of brain derived neurotrophic factor (BDNF) can rescue diseased spiral ganglion neurons in the deafened cochlea, but cessation of treatment can lead to tissue regression to the diseased state [157]. Shepard et al demonstrated that electrical stimulation can be used to maintain cells following completion of neurotrophin delivery over 28 days [158].…”
Section: Control Of Biomolecule Releasementioning
confidence: 99%
“…One previous study in guinea pigs reported accelerated degeneration of SG neurons after cessation of BDNF administration (Gillespie et al 2003), but other reports have shown maintenance of improved neural survival after NT treatment is terminated (Agterberg et al 2009). Another study reported that electrical stimulation maintained improved SG survival for up to 6 weeks after cessation of BDNF delivery in guinea pigs, but neurotrophic effects were observed only in the basal cochlea near the stimulating electrode, and accelerated neural degeneration was seen in the upper cochlear turns .…”
Section: Introductionmentioning
confidence: 99%